"Bicho-grilo de raiz" : estilos de vida entrecruzados em uma tribo de adeptos de alimentação orgânica - Komino, Aline Chima (2017)
The present study aims to build the different lifestyles that intersect in an urban tribe of adepts of organic foods. For this, the concepts of the lifestyle of Giddens (2002) and of Maffesoli (2006) related to the urban tribes are allied. As a data colle